Variabilidad de la secuencia temporal de la cadena cinética en el lanzamiento de balonmano - Gutierrez-Davila, M.; Ortega, M.; Parraga, J.; Campos, J.; Rojas, F. J. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2011)
The aim is to analyze the intraindividual variability of the throw in support realized from nine meters and in presence of a goalkeeper. Four throwers and seven goalkeepers from first Spanish division took part. From the forces of reaction proceeding from the platform, was registered the beginning of the movement of the goalkeeper, whereas the model of the throwing was using video 3D. The variability in the movement pattern faked the goalkeepers and reduced the time of movement. The kinetic chain is a temporary sequence P-D orientated to reducing the excessive stress in the joint of the shoulder. The inertia of the trunk reduced the time of execution and choose the instant of throwing depending on the goalkeeper.